Transcatheter aortic valve implantation with SAPIEN 3 versus surgical aortic valve replacement in patients with symptomatic severe aortic stenosis at low risk of surgical mortality: a cost-utility analysis for Switzerland - Christophe Alain Wyss; Roberto Corti; Thomas Nestelberger; Pascal Candolfi; Alexis Delbaere; Barbara Fischer; Matthias Schwenkglenks; Harry Telser (Swiss Medical Weekly)
AIMS OF THE STUDY: The 2021 European Society of Cardiology Guidelines on valvular heart disease recommend transcatheter aortic valve implantation (TAVI) for patients with symptomatic severe aortic stenosis at low surgical risk and age ≥75 years who are suitable for a transfemoral approach (recommendation class IA) based on two large randomised controlled trials (PARTNER 3 and Evolut Low Risk) comparing transcatheter aortic valve implantation with surgical aortic valve replacement (SAVR). Whether such an approach is cost-effective in Switzerland remains unclear. The aim of this cost-utility analysis was to compare transcatheter aortic valve implantation with SAPIEN 3 versus surgical aortic valve replacement in symptomatic severe aortic stenosis patients at low risk of surgical mortality from the perspective of Swiss compulsory health insurance using data from the PARTNER 3 trial (reflecting specifically the safety and efficacy of the SAPIEN 3 TAVI device).